The path integral representation kernel of evolution operator in Merton-Garman model - Blazhyevskyi, L.F.; Yanishevsky, V.S. (Condensed Matter Physics, 2011)
In the framework of path integral the evolution operator kernel for the Merton-Garman Hamiltonian is constructed. Based on this kernel option formula is obtained, which generalizes the well-known Black-Scholes result. Possible approximation numerical schemes for path integral calculations are proposed. В методi континуального iнтегрування побудовано ядро оператора еволюцiї для гамiльтонiану Мертона-Кармана. На основi ядра отримана формула для цiни опцiону, що узагальнює вiдому формулу Блека-Шоулса. Вказано також на можливi способи наближеного обчислення континуальних iнтегралiв.